Serum leptin levels in patients with premature ejaculation before and after citalopram treatment - Atmaca, M; Kuloglu, M; Tezcan, E; Ustundag, B; Semercioz, A (Wiley, 2003)
OBJECTIVE To evaluate serum leptin levels (an adipocyte hormone involved in the suppression of appetite) in patients with premature ejaculation before and after treatment with citalopram, a selective serotonin reuptake inhibitor, with the hypothesis that leptin levels might become normal during this treatment. PATIENTS AND METHODS The inhibitory effect of serotonin on libido, ejaculation and orgasm is well documented. Although there is no direct evidence of an association involving brain pathways which are related to sexual behaviour, there is an interaction between leptinergic and serotonergic systems. In a previous study serum leptin levels were high in patients with premature ejaculation. The present study comprised 30 patients with premature ejaculation according to the Diagnostic and Statistical Manual of Mental Disorders Third Revised Version. Fifteen patients (group I) were randomly assigned to 8 weeks of citalopram treatment and the remainder (15, group II) received no therapy. The patients were asked to determine the average intravaginal ejaculation latency time, and their fasting serum leptin levels were measured at baseline and after 8 weeks. RESULTS There was no significant difference in the mean intravaginal ejaculation latency time between the groups at baseline; it increased after 8 weeks of treatment with citalopram in group I, to a mean (sd) of 209 (72.1) s, but not in group II. No difference was detected in leptin levels between the groups at baseline, but at 8 weeks they were lower in group I. CONCLUSION As hypothesized, leptin levels decreased in patients with premature ejaculation after treatment with citalopram, and this decrease seemed to be linked to the therapeutic effect. Further experimental studies are needed.
Keywords: leptin; premature ejaculation; serotonin; citalopram